Implementation of Standardized Care for the Medical Stabilization of Patients With Anorexia Nervosa. Issue 5 (26th September 2022) - Shafii, Taraneh; Morrison, Alex; Qu, Pingping; Rutman, Lori; Kaplan, Ron
Abstract : Introduction: Approaches to refeeding patients with anorexia nervosa for medical stabilization vary across institutions, and there is no established standard of care. This study assessed the impact of a refeeding pathway on hospital length of stay and transfer to the psychiatry unit. Methods: This quality improvement intervention sought to standardize care for adolescents with anorexia nervosa at a tertiary care, free-standing children's hospital from Spring 2017 to Fall 2018. The pathway specified admission criteria, nutritional advancement, activity restriction, laboratory monitoring, readiness to transfer to the psychiatry unit, and discharge criteria. Statistical process control analysis was utilized to identify system-level changes over time. We used linear regression to assess pre- and postpathway differences in length of stay and transfer to the psychiatry unit. Results: There were 161 patient encounters for anorexia nervosa admitted for medical stabilization. 84% of the sample were female with median age of 15.2 (IQR 14.0–17.0) years. There was no difference in hospital length of stay between the pre- and postpathway groups. There was a statistically significant increase in the proportion of patients transferred to the psychiatry unit over the study period. Conclusion: Clinical pathway use to deliver standardized care to achieve medical stability for patients with anorexia nervosa did not shorten hospital length of stay. Multiple potentially confounding medical and psychosocial factors may have contributed to this lack of improvement.